2013
DOI: 10.1021/nn305959q
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of Phosphide Nanocrystals into Porous Networks: Formation of InP Gels and Aerogels

Abstract: The applicability of sol-gel nanoparticle assembly routes, previously employed for metal chalcogenides, to phosphides is reported for the case of InP. Two different sizes (3.5 and 6.0 nm) of InP nanoparticles were synthesized by solution-phase arrested precipitation, capped with thiolate ligands, and oxidized with H₂O₂ or O₂/light to induce gel formation. The gels were aged, solvent-exchanged, and then supercritically dried to obtain aerogels with both meso- (2-50 nm) and macropores (>50 nm) and accessible sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 36 publications
0
36
0
Order By: Relevance
“…In this case, common synthesis methods are based on nucleation-to-growth or linker-* coasne@mit.edu driven assembly of building units where the final structures can reach a state close to equilibrium. Obtaining in a controlled way such materials, which exhibit a large surface area from ∼10 to 500 m 2 /g made up of highly polarizable atoms, can lead to breakthroughs for applications relying on the surface properties of the host compound (photocatalysis and gas separation, for instance) [14][15][16]. Recently, chalcogels have been demonstrated to be efficient sorbents for environmental remediation from gaseous and water waste media [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In this case, common synthesis methods are based on nucleation-to-growth or linker-* coasne@mit.edu driven assembly of building units where the final structures can reach a state close to equilibrium. Obtaining in a controlled way such materials, which exhibit a large surface area from ∼10 to 500 m 2 /g made up of highly polarizable atoms, can lead to breakthroughs for applications relying on the surface properties of the host compound (photocatalysis and gas separation, for instance) [14][15][16]. Recently, chalcogels have been demonstrated to be efficient sorbents for environmental remediation from gaseous and water waste media [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Porous semiconductors have been recognized as a unique class of nanomaterials due to their low density, high surface area, and large open pores . Typically, these materials are formed via the sol–gel assembly of semiconductor nanoparticles into aerogel networks by chemical bridging of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20][21] In these materials, the ultrathin semiconductor inorganic 2D slabs are intercalated with organic diamines, providing not only an ideal model system for fundamental study but also free-standing quantum wells for optoelectronic applications.Porous semiconductors have been recognized as a unique class of nanomaterials due to their low density, high surface area, and large open pores. [22][23][24][25][26][27][28][29][30][31][32][33] Typically, these materials are formed via the sol-gel assembly of semiconductor nanoparticles into aerogel networks by chemical bridging of nanoparticles. For example, Arachchige and Brock reported that the thiolate ligands capping on the surfaces of nanoparticles are oxidized to network nanoparticles together.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Aerogels are highly porous materials often formed by synthesizing sol-gel metal oxides(While metal oxide aerogels are very common, carbon and other types of aerogels have been synthesized. One example is InP aerogels) 10 and drying these sol-gels in such a way that the porous solid matrix is left unchanged [11][12][13][14] . All of the pores in solid aerogels result in much available surface area making aerogels extremely useful for any applications where surface reactions are important.…”
Section: Introductionmentioning
confidence: 99%